Respuestas

  • Usuario de Brainly
2013-06-11T02:01:06+02:00
(x - 2)² + (x +1 )² = x + 7
x² - 4x + 4+ x² + 2x + 1 = x +7
2x² -  2x + 5 = x + 7                     igualamos a cero
2x² - 2x + 5 -x - 7 = 0
2x² - 3x - 2 = 0
aplicamos bascara
      –b ± √ b² – 4ac
x = ▬▬▬▬▬▬▬             donde a=2              b= - 3          c= - 2
              2a


      3 ± √ 9 + 16
x = ▬▬▬▬▬▬▬
            4

       3  ± √ 25
x = ▬▬▬▬▬▬▬
              4

      3 ± 5
x = ▬▬▬▬
         4

x1= 8/4 → x1 = 2
x2= - 2/4 → x2= - 1/2

espero que te sirva,salu2!!!!